Prediction of Land Erosion Events in the Down Stream Kreung Meureubo Watershed West Aceh District - Muhammad Ikhsan; Meylis Safriani; Cut Suciatina Silvia; Refvina Dari (Master Program of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
This study aims to predict the occurrence of erosion in the downstream Krueng Meureubo watershed, West Aceh Regency. Erosion is the loss of topsoil due to rain splash which is analyzed as a factor of rain erosivity, but the occurrence of erosion is not necessarily calculated by the occurrence of rain alone, but many other factors, such as soil erodibility, slope and length of land, land cover and the presence or absence of land conservation efforts. the. The Krueng Meurebo watershed shows a large sediment transport, with an indication that the river is getting shallower caused by sediment deposition at the riverbed, this sediment comes from sediment carried through the process of soil erosion. The method used in analyzing the occurrence of soil erosion in this study is the USLE method and uses a Geographic Information System (GIS). The results obtained are the distribution of erosion rate values in 228 polygons, with the largest erosion rate value occurring in polygon 1 with an erosion rate of 8495.308 tons/ha/year. The smallest erosion rate occurs in polygons 30, 34, 35, 179, and 180, with an erosion rate of 0 meaning that there is no land erosion event, which occurs in organosol and glehumus and regosol soil types, land cover is settlements and water bodies. It is concluded that the occurrence of erosion in a land is very dependent on the type of soil and the type of land cover. It is recommended for land with large erosion events to take serious land conservation actions so that erosion events can be minimized and do not occur continuously which of course can cause the watershed to become critical. Conservation efforts can be carried out in various ways, one of which is by vegetative means using plants that can reduce the rate of soil erosion.